KEBIJAKAN PENGELOLAAN HUTAN DAN KEMISKINAN MASYARAKAT (STUDI KASUS DI NAGARI GARABAK DATA DAN NAGARI BUKIK KANDUANG, KABUPATEN SOLOK) - Hidayatul Fajri (Yogyakarta State University, 2015)
This study discusses forest management by local communities and society of Nagari Garabak Data and Nagari Bukik Kanduang Solok Regency of West Sumatra Province. Nagari Garabak Data is a village located in a protected forest area with the acquisition entirely in the hands of the state while in Nagari Bukik Kanduang forest is managed and controlled by people with a form of community forests (communal forest). Principal argument of this study that differences in the management model of the village causing differences in poverty communities. The purpose of this research is to understand forest management in both villages and analyze the impact of the forest management against poverty. Key Word: Forest Management, Poverty Peoples, Ulayat, Access